Prognostic value of programmed cell death ligand-1 expression in patients with bladder urothelial carcinoma undergoing radical cystectomy: A meta-analysis - Zhang, Jindong; Song, Liangdong; Zhu, Huixuan; Liu, Qinyuan; Wang, Delin (Frontiers in Immunology, 2022)
Abstract Background: Radical cystectomy and removal of pelvic lymph nodes (RC-PLND) is a recommended treatment for high-risk non-muscle-invasive and muscle-invasive non-metastatic bladder cancer (BC). However, 50% of patients relapse after RC-PLND. This study aimed to evaluate the effect of programmed cell death ligand-1 (PD-L1) on the prognosis of bladder urothelial carcinoma (BUC) after RC-PLND. Methods: We present this meta-analysis according to the Preferred Reporting Items for Systematic Review and Meta-Analyses Guidelines. The main outcomes were overall survival (OS), recurrence-free survival (RFS), and cancer-specific survival (CSS) of 3 and 5 years after RC-PLND. Results: Overall, 11 studies and 1393 BUC cases were included in our meta-analysis. In tumor cells (TCs), the PD-L1 negative group had statistically significant advantage in 5-year OS (risk ratio [RR]: 0.85, 95% confidence interval [CI]: 0.74–0.97, P = 0.02), RFS (RR: 0.76, 95% CI: 0.58–0.99, P = 0.04), and CSS (RR: 0.73, 95% CI: 0.58–0.92, P = 0.009) compared with the PD-L1 positive group. But, no statistically significant difference in 5-year OS and RFS was observed between the PD-L1 negative and positive groups in tumor-infiltrating immune cells. Conclusions: Our study found that patients with BUC who tested positive for PD-L1 in TCs had a poor prognosis after RC-PLND. PD-1 or PD-L1 inhibitors could be used as a adjuvant medication for patients with BUC after RC-PLND who exhibit PD-L1 overexpression in TCs. Registration: This study was registered in the International Prospective Register of Systematic Reviews (number: CRD42022301424).